Influence of competitive schedule on subjective and objective sleep duration in professional female soccer players - Knott, S. M.; Anderson, R.; Tarnowski, C. A.; Brown, L. R.; Carter, J. M.; Moss, S. L.; Bright, N.; Randell, R. K.; Rollo, I. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: To support performance, recovery and physical and mental health athletes are advised to achieve approximately eight hours of sleep. During the competitive season it is important to understand how sleep varies to inform sleep and recovery recommendations. In professional female soccer players there is limited sleep data available. In addition, no studies have compared objective and subjective measures of sleep duration within a comprehensive competitive soccer schedule. This information is important as objective measures are expensive and often cost prohibitive to teams. Therefore, the aims of this study were to 1) determine the impact of competitive schedule on sleep duration, 2) compare objective and subjective measures of sleep duration in professional female soccer players.